Differentially Amplified Repetitive Sequences Among Aegilops tauschii Subspecies and Genotypes - Ebrahimzadegan, Rahman; Orooji, Fatemeh; Ma, Pengtao; Mirzaghaderi, Ghader (Frontiers in Plant Science, 2021)
Genomic repetitive sequences commonly show species-specific sequence type, abundance, and distribution patterns, however, their intraspecific characteristics have been poorly described. We quantified the genomic repetitive sequences and performed single nucleotide polymorphism (SNP) analysis between 29 Ae. tauschii genotypes and subspecies using publicly available raw genomic Illumina sequence reads and used fluorescence in situ hybridization (FISH) to experimentally analyze some repeats. The majority of the identified repetitive sequences had similar contents and proportions between anathera, meyeri, and strangulata subspecies. However, two Ty3/gypsy retrotransposons (CL62 and CL87) showed significantly higher abundances, and CL1, CL119, CL213, CL217 tandem repeats, and CL142 retrotransposon (Ty1/copia type) showed significantly lower abundances in subspecies strangulata compared with the subspecies anathera and meyeri. One tandem repeat and 45S ribosomal DNA (45S rDNA) abundances showed a high variation between genotypes but their abundances were not subspecies specific. Phylogenetic analysis using the repeat abundances of the aforementioned clusters placed the strangulata subsp. in a distinct clade but could not discriminate anathera and meyeri. A near complete differentiation of anathera and strangulata subspecies was observed using SNP analysis; however, var. meyeri showed higher genetic diversity. FISH using major tandem repeats couldn’t detect differences between subspecies, although (GAA)10 signal patterns generated two different karyotype groups. Taken together, the different classes of repetitive DNA sequences have differentially accumulated between strangulata and the other two subspecies of Ae. tauschii that is generally in agreement with spike morphology, implying that factors affecting repeatome evolution are variable even among highly closely related lineages.